2019
DOI: 10.3390/plants8060168
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Resistance to Leaf Fall Disease Caused by Phytophthora palmivora in Rubber Tree Seedling by Sargassum polycystum Extract

Abstract: The brown seaweed (Sargassum polycystum C. Agardh-Sargassaceae) extract was examined for its bioelicitor properties in the rubber tree seedling (Hevea brasiliensis (Willd. ex A.Juss.) Müll.Arg. - Euphorbiaceae) and its application to reduce the leaf fall disease caused by Phytophthora palmivora (Edwin John) Butler, 1917 (Peronosporaceae). The major purpose of this study was to apply this seaweed extract (SWE) to improve the disease resistance in rubber tree seedling compared to a chemical fungicide (1% metalax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Among the clones studied, the clone RRII 105 and GT1 were reported as resistant clones to phytophthora leaf fall on prophylactic spraying (Edathil et al, 2000). In a recent report (Khompatara et al, 2019), Sargassum polycystum, a seaweed extract, was found effective to increase resistance to the Phytophthora mediated leaf fall disease in rubber seedlings. Bharat et al (2018) reported that an alga, Sargassum polycystum, has the elemental concentration of sodium (85.3 mg L -1 ), chlorine ( 75.02 mg L -1 ) and calcium (69 mg L -1 ) in higher quantity and among this Ca was in appreciable quantity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Among the clones studied, the clone RRII 105 and GT1 were reported as resistant clones to phytophthora leaf fall on prophylactic spraying (Edathil et al, 2000). In a recent report (Khompatara et al, 2019), Sargassum polycystum, a seaweed extract, was found effective to increase resistance to the Phytophthora mediated leaf fall disease in rubber seedlings. Bharat et al (2018) reported that an alga, Sargassum polycystum, has the elemental concentration of sodium (85.3 mg L -1 ), chlorine ( 75.02 mg L -1 ) and calcium (69 mg L -1 ) in higher quantity and among this Ca was in appreciable quantity.…”
Section: Discussionmentioning
confidence: 97%
“…The enhanced resistance may be due to high Ca content in these clones. Disease control using chemical fertilizers usually have an adverse effect on the environment, soil and a reason for toxicity of living beings associated (Khompatara et al, 2019). In consideration of these, the identification of inherently resistant clones is more beneficial and easier as a control measure.…”
Section: Discussionmentioning
confidence: 99%
“…The foliar application of an extract prepared by the alkali treatment of Sargassum polycystum was reported to reduce leaf fall disease caused by Phytophthora palmivora by inducing systemic acquired resistance. The application of the extract induced enzymatic activities of catalase, endo-1,3- d -glucanase, and peroxidase in response to P. palmivora [ 166 ].…”
Section: Seaweeds: Sources Of Extracts Used As Biostimulantsmentioning
confidence: 99%
“…The colony counts in the soil and metabolic activities of soil microbes were found to increase following SEs applications, which contributed to increase plant root and shoot growth ( Alam et al, 2013 ). SEs increased the absorption of soil nutrients by plants, stimulated the growth of crops, increased yield ( Renaut et al, 2019 ; Boukhari et al, 2020 ), and enhanced plant resistance to biotic ( Machado et al, 2014 ; Ben Salah et al, 2018 ) and abiotic stress ( Bradáčová et al, 2016 ; Cabo et al, 2019 ; Khompatara et al, 2019 ). For example, SEs sprayed on onion grown under water stress significantly increased N, P, and K uptake by 116, 113, and 93% compared to the unsprayed plants ( Almaroai and Eissa, 2020 ).…”
Section: Introductionmentioning
confidence: 99%